2020
DOI: 10.21203/rs.3.rs-40416/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Numerical and experimental study on air thrust foil bearing performance with improved structural model based on real-time taper inlet height

Abstract: Abstract Air thrust foil bearings are key bearings of micro turbo-machinery (such as micro gas turbines, turbo blowers, and air compressors). The bearing load capacity is affected by many factors, and the taper inlet height of bearing structure is closely related to the load capacity. In many previous literature the taper inlet height, as a constant value, was used to calculate film thickness distribution. However, the reality is that the foil will be squeezed by the pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…Static tests on foil thrust bearings (FTB) with viscoelastic support illustrated an increase in structural stiffness with an increase in axial load while dynamic tests depicted small amounts of axial vibration of the rotor at higher speeds [27]. Novel bearing test rig developed by Xu et al [28] consisted a high speed motor (speeds ranging from 15,000 rpm to 28,000 rpm) with a piston loading device for measuring bearing thrust load for an optimized taper height of the top foil, besides the test results being compared with the computational model developed by them.…”
Section: Experimental Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Static tests on foil thrust bearings (FTB) with viscoelastic support illustrated an increase in structural stiffness with an increase in axial load while dynamic tests depicted small amounts of axial vibration of the rotor at higher speeds [27]. Novel bearing test rig developed by Xu et al [28] consisted a high speed motor (speeds ranging from 15,000 rpm to 28,000 rpm) with a piston loading device for measuring bearing thrust load for an optimized taper height of the top foil, besides the test results being compared with the computational model developed by them.…”
Section: Experimental Reviewmentioning
confidence: 99%
“…7. Fang Xu [28] showed that 0.2 mm TF and BF mounted on AFTB of 36 mm BD (FSA = 3000 mm 2 ) with a taper height of 20 microns had load capacity of 60 N, 73 N, 78 N, and 100 N corresponding to 15 krpm, 21 krpm, 25 krpm, and 28 krpm speeds. 8.…”
Section: Comparative Surveymentioning
confidence: 99%